IMPLEMENTASI LEAN MANAGEMENT PADA OPERASI BISNIS DIGITAL UNTUK MENINGKATKAN EFISIENSI DAN PRODUKTIVITAS : STUDI LITERATUR - Sutopo, Sutopo; Sudianto, Sudianto (Journal of Information Systems Management and Digital Business, 2025)
Implementation of Lean Management in digital business is an approach that aims to increase efficiency and productivity by identifying and eliminating waste, and maximizing the value provided to customers. The purpose of this study is to explore the application of Lean Management in the context of digital business operations, and how Lean principles can be adapted to address the unique challenges and dynamics of the digital environment. This study is a literature study that examines various academic sources, articles, and case studies relevant to the topic. This literature study identifies several important aspects in the implementation of Lean Management in digital business, including basic Lean principles such as value, flow, withdrawal, and the creation of flow without waste. In the digital context, waste can not only be found in the physical production aspect, but also in the process of managing data, time, and interactions between users and systems. The main focus of this study is how Lean Management can be used to improve the flow of information and optimize the use of technology in digital business, which can ultimately increase productivity and operational efficiency. Based on the results of the literature analysis, it was found that the application of Lean Management in digital business can provide many benefits, including reducing operational costs, increasing service speed, and improving customer experience. In addition, the implementation of Lean also allows companies to be more responsive to changes in market needs and technological developments. However, the implementation of Lean Management in digital businesses also faces its own challenges, such as dependence on technology and data, difficulties in measuring waste in software-based systems, and differences in the approaches required between traditional and digital industries. This study also discusses the importance of involving all stakeholders in the process of changing organizational culture needed to implement Lean effectively. The success of Lean implementation in digital businesses depends on the company's ability to adapt Lean principles to existing technologies, as well as building collective awareness of the importance of efficiency and productivity. In conclusion, this study suggests that digital companies consider implementing Lean Management as a strategy to improve operational efficiency and increase competitiveness in an increasingly dynamic market.